Building Design Impacts and Climate Resilience in Katsina State: A Systematic Review of Sustainable Architectural Practices in Hot-Dry Climates - Emmanuel, Uma Helen; Abdullahi, Abubakar; Wurma, Iliyasu Aliyu (Journal of Science Research and Reviews, 2025)
Katsina State in northern Nigeria faces significant challenges from its hot-dry Sahelian climate, intensified by climate change. This systematic review synthesizes literature on how building design choices influence environmental, social, economic, and resilience outcomes. Traditional Hausa architecture, with features like thick mud walls and courtyards, provides effective passive cooling, while modern concrete designs often exacerbate overheating and energy demands. Barriers to sustainable practices include limited awareness and weak policy enforcement. Flood vulnerability further compounds risk in many areas. The review highlights research gaps in localized empirical studies and recommends hybrid vernacular-modern approaches, updated building codes, and capacity building to enhance climate resilience.
Keywords: Climate resilience; Sustainable architecture; Hot-dry climate; Hausa vernacular; Passive cooling; Katsina State; Nigeria